Does Competition Affect Truth Telling? An Experiment with Rating Agencies - Rabanal, Jean Paul; Rud, Olga A (Review of Finance, 2018)
Abstract We use an experimental approach to study the effect of market structure on the incidence of misreporting by credit rating agencies. In the game, agencies receive a signal regarding the type of asset held by the seller and issue a report. The sellers then present the asset, with the report if one is solicited, to the buyer for purchase. We find that competition among rating agencies significantly reduces the likelihood of misreporting.